2018
DOI: 10.1111/1753-6405.12822
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette use in New South Wales, Australia: reasons for use, place of purchase and use in enclosed and outdoor places

Abstract: E-cigarettes are being used by a small percentage of the NSW population. Reasons for e-cigarette use varied with smoking status. Different sociodemographic characteristics were associated with ever and past 30-day use of e-cigarettes. E-cigarettes are being used in areas that are covered by smoke-free legislation. Implications for public health: Given e-cigarettes are being used in smoke-free areas, policy-makers could take a precautionary approach by including e-cigarette use under smoke-free legislation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…40 A study from Australia in 2016 showed that among 66 current electronic cigarette users, 15% vaped in restaurants and bars and 28% in workplaces. 2 Finally, in a Spanish study based on 600 electronic cigarette users, 33% had used electronic cigarettes in workplaces, 69% in restaurants or bars, 3% on public transport, and 55% in nightclubs. 15 Compared to the above studies, in general, we found higher prevalence rates of use in smoke-free indoor environments, probably because our sample included mainly relatively heavy smokers looking for smoking cessation support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 A study from Australia in 2016 showed that among 66 current electronic cigarette users, 15% vaped in restaurants and bars and 28% in workplaces. 2 Finally, in a Spanish study based on 600 electronic cigarette users, 33% had used electronic cigarettes in workplaces, 69% in restaurants or bars, 3% on public transport, and 55% in nightclubs. 15 Compared to the above studies, in general, we found higher prevalence rates of use in smoke-free indoor environments, probably because our sample included mainly relatively heavy smokers looking for smoking cessation support.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic cigarettes are electronic devices containing a liquid heated to generate an inhalable vapor, which may contain nicotine. 1,2 In most high-income countries, electronic cigarettes were introduced into the market around 2010, and since then they have gained popularity worldwide. 1,3,4 In Europe, after an initial rapid spread of electronic cigarette use, 5 its use increased only slightly, with the proportion of adult regular users rising from 1.5% in 2014 to 1.8% in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…However, e-cigarettes do not burn tobacco. Instead they vaporise e-liquid, a solution that is typically composed of nicotine, propylene glycol (PG) and vegetable glycerine (VG) often supplemented with various flavouring compounds and/or ethanol [1][2][3]. The main benefit of ecigarettes is that they enable nicotine intake without exposure to many other, often hazardous, chemicals which are normally present in tobacco cigarettes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Heuristics based on sensory perceptions, and interpretations of others’ reactions, informed beliefs about SHA and shaped norms that guided vaping practices. The absence of information documenting SHA’s potential risks led participants to extrapolate that it was not only safer than SHS, but carried few, if any, risks and was therefore safe to bystanders 34. While many scientists treat inadequate information conservatively and call for cautious and protective regulation, our participants interpreted the information vacuum as a sign of SHA’s safety.…”
Section: Discussionmentioning
confidence: 91%